2021
DOI: 10.3390/cancers13061342
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Evolution and Seed and Soil Mechanism in Pancreatic Metastases of Renal Cell Carcinoma

Abstract: In metastatic renal cell carcinoma, pancreatic metastases can appear in two clinical manifestations: (a) very rarely as isolated pancreatic metastases and (b) in the context with multi-organ metastatic disease. Both courses are characterised by rare, unusual clinical features. For isolated pancreatic metastases, the literature shows no effect on survival in all 11 publications that examined the effect of singular versus multiple pancreatic metastases; a lack of effect on survival time was also present in all 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 189 publications
(425 reference statements)
0
15
0
Order By: Relevance
“…The components of the tumor microenvironment include all of the nonmalignant stroma cells inside the tumor other than the tumor cells, including fibroblasts, endothelial cells, immune cells, and platelets [5,6]. Paget proposed the "seed and soil" theory in 1889 and conducted an indepth analysis of the molecular characteristics of "seeds" (cancer cells) [7][8][9][10][11]. By studying the "soil" formed by cancer cells and host immune cells, scientists found that immune cells usually bind to cancer cells and obtain specific biological phenotypes via interactions with them.…”
Section: Introductionmentioning
confidence: 99%
“…The components of the tumor microenvironment include all of the nonmalignant stroma cells inside the tumor other than the tumor cells, including fibroblasts, endothelial cells, immune cells, and platelets [5,6]. Paget proposed the "seed and soil" theory in 1889 and conducted an indepth analysis of the molecular characteristics of "seeds" (cancer cells) [7][8][9][10][11]. By studying the "soil" formed by cancer cells and host immune cells, scientists found that immune cells usually bind to cancer cells and obtain specific biological phenotypes via interactions with them.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of isolated PM in RCC involves a particular “seed and soil” pathway that explains the selective development of metastases in the pancreas by embolized cells from the primary tumor. This specific metastatic mechanism creates a frame for uniform distribution of metastatic lesions across the pancreas, independent of the RCC site, and similar outcomes in singular versus multiple, synchronous versus metachronous isolated PM [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a distinct case of RCC, isPMRCC has a clinical hallmark of confinement to the pancreas while the other organs are left unaffected for a long duration. This kind of organotropism may be explained based on seed and soil theory, according to which the metastatic process is determined by the interaction between the tumor cells (seed) and the host organism (soil) ( 17 , 18 ). Research on microRNA has identified that miRNAs regulate the metastatic potential of tumor cells and explain the seed and soil concept biochemically ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%